2013
DOI: 10.3126/njms.v2i2.8941
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice regarding Cervical Cancer Screening Amongst Women visiting Tertiary Centre in Kathmandu, Nepal

Abstract: Background: Cervical cancer is one of the commonest cancers in Nepal. Fortunately, it is preventable by detecting precancerous lesions and early invasive cancers by various screening tools. Screening can be possible if women are aware of the problem and if they have positive attitude .Therefore this study was conducted to find out about the knowledge, attitude and practice of cervical cancer in Nepalese women attending a tertiary level hospital in Nepal. Methods: A cross-sectional questionnaire based study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
70
13
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(119 citation statements)
references
References 10 publications
29
70
13
1
Order By: Relevance
“…Similarly, women in late childbearing age have cumulative knowledge about health care issues and opportunities of more hospital visits than younger women, which means they have more opportunity to undertake pap smear test with each hospital visit. A Turkish study, an Indian study and another study done in Nepal had similar finding regarding late child-bearing age (Bekar et al, 2013;Shekhar et al, 2013a;Shrestha et al, 2013). In contrast to our study, these two studies from Nepal and India and another study from Erzurum, Turkey showed women with high parity to have significantly better KAP values (Karabulutlu, 2013).…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…Similarly, women in late childbearing age have cumulative knowledge about health care issues and opportunities of more hospital visits than younger women, which means they have more opportunity to undertake pap smear test with each hospital visit. A Turkish study, an Indian study and another study done in Nepal had similar finding regarding late child-bearing age (Bekar et al, 2013;Shekhar et al, 2013a;Shrestha et al, 2013). In contrast to our study, these two studies from Nepal and India and another study from Erzurum, Turkey showed women with high parity to have significantly better KAP values (Karabulutlu, 2013).…”
Section: Discussioncontrasting
confidence: 54%
“…Only one article was found in the world wide web in which 65.7% and 42.9% of participants were found to be aware of cervical cancer and cervical pap smear test respectively in Kathmandu, Nepal. Only 10.5% of all the participants had at least one pap smear test done in that research (Shrestha et al, 2013). Despite more women being aware of cervical cancer and pap smear test, :http://dx.doi.org/10.7314/APJCP.2014.15.20.8905 Association of Knowledge, Attitude and Demographic Variables with Cervical Pap Smear Practice in Nepal utilization of the test is lower than in our study.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations